Glass and article comprising the same

By adjusting the oxide reference composition of the glass, especially increasing the content of components such as SiO2, B2O3, P2O5, etc., the problem of insufficient water repellency of existing glass materials is solved, and the high water repellency of glass is achieved, and the wetting angle relative to water reaches more than 60°.

CN119822632APending Publication Date: 2025-04-15HOYA CORPORATION

Patent Information

Application Number
CN202510131101.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-10-23
Filing Date
2021-03-25
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing glass materials lack water repellency, which makes it difficult to effectively utilize their physical properties when high water repellency is required, and it is difficult for the existing method to form a water repellent coating film with high sustainability and excellent uniformity.

Method used

By adjusting the oxide reference composition of the glass, especially increasing the content of components such as SiO2, B2O3, P2O5, etc., and controlling the proportion of other oxide components, the water repellency of the glass is improved. Specifically, the SiO2 content is 0 to 25%, the B2O3 content is 0 to 35%, the P2O5 content is 0 to 30%, and the total content of SiO2, B2O3 and P2O5 is 10 to 45%, so as to achieve high water repellency of the glass.

Benefits of technology

The high water repellency of glass is achieved, and the wetting angle relative to water reaches above 60°, which significantly improves the water repellency performance of glass, making it suitable for various applications where high water repellency is required.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005261571980000181
    Figure BDA0005261571980000181
  • Figure BDA0005261571980000191
    Figure BDA0005261571980000191
  • Figure BDA0005261571980000201
    Figure BDA0005261571980000201
Patent Text Reader

Abstract

The present invention provides a glass that does not include glass for an optical element selected from a lens and a prism and glass for an optical fiber, the glass containing each glass component in a defined amount in an oxide-based glass composition, and having a wetting angle with respect to water of 60 DEG or more.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of an application with a filing date of March 25, 2021, application number 202180023257.7, and invention name “Glass and articles containing glass”. Technical Field

[0002] The present invention relates to glass and articles comprising glass. Background Art

[0003] Glass is used for various articles that want to effectively utilize its physical properties (e.g., transparency, chemical, mechanical, thermal stability, etc.). On the other hand, in various fields, articles with high water repellency are desired, but it is known that glass is generally a substance that is easily wetted and has low water repellency. Therefore, for articles that require water repellency, water repellency is imparted by forming a water repellent coating on the glass surface, performing micro-concave-convex processing on the glass surface (e.g., see Patent Document 1), etc.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2017-001327 Summary of the invention

[0007] Problem that the invention aims to solve

[0008] As an example, for a car windshield, it is important to improve the water repellency of the windshield surface in order to easily remove attached water droplets in order to ensure the driver's field of vision. For example, for tableware, it is desirable to have high water repellency from the viewpoint of inhibiting the adhesion of scale. In addition, for a measuring cylinder, the meniscus generated by the high wettability of the glass makes it difficult to accurately measure water.

[0009] However, in the case of imparting water repellency by the existing methods as described above (formation of water repellent coating, micro-concave-convex processing, etc.), it is difficult to directly and effectively utilize the physical properties of glass. In addition, for example, for imparting water repellency by forming a water repellent coating, it is not easy to form a coating film with high water repellency and excellent uniformity. In contrast, if the water repellency of the glass itself can be improved, the excellent physical properties of the glass can be effectively utilized to improve the performance of various water repellent articles. However, in the past, no method for improving the water repellency of the glass itself was shown, and glass with high water repellency has not been put into practical use.

[0010] An object of one embodiment of the present invention is to provide glass having high water repellency.

[0011] Solutions to the problem

[0012] One embodiment of the present invention relates to a glass,

[0013] In the oxide-based glass composition,

[0014] Based on quality standards,

[0015] SiO2 content is 0~25%,

[0016] B2O3 content is 0~35%,

[0017] P2O5 content is 0~30%,

[0018] The total content of SiO2, B2O3 and P2O5 (SiO2+B2O3+P2O5) is 10-45%,

[0019] Al2O3 content is 0~15%,

[0020] Li2O content is 0-2%,

[0021] Na2O content is 0-10%,

[0022] K2O content is 0-10%,

[0023] Rb2O content is 0-5%,

[0024] Cs2O content is 0-5%,

[0025] The total content of Li2O, Na2O, K2O, Rb2O and Cs2O (Li2O+Na2O+K2O+Rb2O+Cs2O) is 0-15%,

[0026] MgO content is 0-20%,

[0027] CaO content is 0-25%,

[0028] SrO content is 0-25%,

[0029] BaO content is 0-30%,

[0030] ZnO content is 0-60%,

[0031] La2O3 content is 0~50%,

[0032] Y2O3 content is 0~15%,

[0033] Gd2O3 content is 0~25%,

[0034] Yb2O3 content is 0~10%,

[0035] CeO2 content is 0~10%,

[0036] ZrO2 content is 0~15%,

[0037] TiO2 content is 0-20%,

[0038] SnO2 content is 0~10%,

[0039] Nb2O5 content is 0~30%,

[0040] Ta2O5 content is 0~15%,

[0041] WO3 content is 0-15%,

[0042] Bi2O3 content is 0~20%,

[0043] Ga2O3 content is 0~5%,

[0044] In2O3 content is 0~5%,

[0045] GeO2 content is 0~5%,

[0046] The content of Sb2O3 is 0-1%,

[0047] The total content of ZnO, MgO, CaO, SrO, BaO, Y2O3, La2O3, Gd2O3, ZrO2, TiO2, Al2O3, Nb2O5, Ta2O5, WO3 and Bi2O3 (ZnO+MgO+CaO+SrO+BaO+Y2O3+La2O3+Gd2O3+ZrO2+TiO2+Al2O3+Nb2O5+Ta2O5+WO3+Bi2O3) is 55-90%,

[0048] Fe2O3 content is 0~10%,

[0049] The total content of V2O5, Cr2O3, MnO2, Co2O3, NiO, CuO, MoO, Au2O3 and Ag2O (V2O5+Cr2O3+MnO2+Co2O3+NiO+CuO+MoO+Au2O3+Ag2O) is 0-3%,

[0050] Furthermore, the wetting angle of the glass relative to water is greater than 60°.

[0051] The above-mentioned glass does not include glass used for optical elements selected from lenses and prisms and glass used for optical fibers.

[0052] In addition, one embodiment of the present invention relates to an article comprising glass, wherein the article is selected from window materials, windshields, cover glasses, mirrors, tableware, physical and chemical experimental instruments, cooking utensils, washbasins, toilet bowls, tombstones, decorations, arts and crafts, glass fibers and glass fiber molded bodies, the glass having the above-mentioned glass composition, and the wetting angle of the glass relative to water is greater than 60°.

[0053] Effects of the Invention

[0054] According to one embodiment of the present invention, glass having high water repellency and an article including the glass having high water repellency can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 The spectral transmittance curve obtained for the glass of Example 40 is shown.

[0056] Figure 2 The spectral transmittance curve obtained for the glass of Example 41 is shown.

[0057] Figure 3 The spectral transmittance curve obtained for the glass of Example 42 is shown.

[0058] Figure 4 The spectral transmittance curve obtained for the glass of Example 43 is shown.

[0059] Figure 5 The spectral transmittance curve obtained for the glass of Example 44 is shown.

[0060] Figure 6 The spectral transmittance curve obtained for the glass of Example 45 is shown.

[0061] Figure 7 The spectral transmittance curve obtained for the glass of Example 46 is shown.

[0062] Figure 8 The spectral transmittance curve obtained for the glass of Example 47 is shown. DETAILED DESCRIPTION

[0063] [Glass]

[0064] Hereinafter, the above-mentioned glass will be described in more detail.

[0065] Regarding the water repellency of glass, it is believed that the wetting angle of soda-lime glass, which is commonly widely used in window glass, bottle glass, etc., relative to water is less than 40°. Soda-lime glass is a glass containing about 70% by mass of SiO2. In addition, in hard glass used for tableware, chemical experiment instruments, etc., the SiO2 content exceeds 70% by mass. Therefore, for the glass used in the articles expected to be water repellent in the past, SiO2 basically becomes a network former. Therefore, even if the modified oxide changes to some extent, the surface energy only produces a slight difference, so the concept of "glass = hydrophilicity" is usually fixed. The hydrophilicity and water repellency of water are determined by the surface free energy of the substance. Water repellency is produced by not hindering the surface tension of water, and the surface energy of SiO2, which is a glass-forming oxide, is relatively large, so the wettability of water is improved.

[0066] On the other hand, various components can be introduced into glass. For example, optical glass that requires specific refractive index characteristics as lenses and prisms has previously used glasses of various composition systems, such as glasses that use B2O3 and P2O5 as network formers in addition to SiO2. For optical glass, anti-reflection coatings are implemented to reduce surface reflections. In addition, lenses with different characteristics are joined. In this case, there is no need to specifically adjust the surface characteristics of the glass itself. Therefore, water repellency is not required in optical glass and has not been studied.

[0067] In contrast, the inventors have repeatedly conducted in-depth research, and in the process, have obtained a new insight that the wettability of glass can be greatly changed by adjusting the glass composition. In detail, it has been found that the wettability of glass can be adjusted by adjusting the content of components that have a greater impact on wettability. More specifically, it has been clarified that the wettability of glass can be adjusted by containing a large amount of components that reduce surface energy, components that have low reactivity to water, and low solubility, while suppressing the content of components that have high surface energy, high polarity, and high chemical reactivity with water. Moreover, based on the composition adjustment method for improving the water repellency of glass thus discovered, the inventors have further repeatedly conducted in-depth research, and as a result, obtained glass with high water repellency and suitable for practical use, namely the above-mentioned glass.

[0068] Hereinafter, the above-mentioned glass will be described in more detail.

[0069] <Glass composition>

[0070] In the present invention and this specification, the glass composition is expressed on the basis of the oxide of the cationic component of the glass. Here, the "glass composition on the basis of oxide" means the glass composition obtained by converting the glass raw materials into substances that are completely decomposed during melting and exist in the form of oxides in the glass. In addition, unless otherwise specified, the glass composition is expressed on the basis of mass (mass %, mass ratio).

[0071] The various components constituting the glass can be quantitatively determined by a known method, such as inductively coupled plasma emission spectrometry (ICP-AES), inductively coupled plasma mass spectrometry (ICP-MS), etc. The content of each element (mass %) contained in the glass can be obtained by dividing the content of the element (mass %) by the atomic weight, and the content of each element expressed in mole % can be calculated using this value, and the content in the glass composition converted to oxide (unit: mass %) can be calculated.

[0072] For anionic components, the anionic components contained in the glass can be identified and quantified by known analytical methods, such as ion chromatography, non-dispersive infrared absorption method (ND-IR), etc. For anionic components other than oxygen, the content of anions % can be obtained by known methods. "Anion %" refers to the value calculated by "(the number of anions of interest / the total number of anions of the glass component) × 100", which is the molar percentage of the amount of anions of interest relative to the total amount of anions. On the other hand, in the present invention and this specification, for the content of oxygen, when no anionic components other than oxygen are detected by analysis using known methods, all of the anionic components (i.e., 100 anion %) can be set as oxygen ions. In contrast, when one or more other anionic components are detected in addition to oxygen by analysis using known methods, as the content of oxygen, the content (unit: anion %) calculated by the following method based on the valence of the cationic components contained in the glass and the content in terms of cation % and the valence of the anionic components other than oxygen and the content in terms of anion % is used. That is, based on the results of identification and quantitative analysis using a known method, the total of "valence × content" (hereinafter referred to as "total valence of cations") is calculated for the cationic components contained in the glass. For the anionic components other than oxygen, the total of "valence × content" (hereinafter referred to as "total valence of anions other than oxygen") is also calculated based on the results of identification and quantitative analysis using a known method. The value calculated in the form of "[(total valence of cations) - (total valence of anions other than oxygen)] / 2" based on the value calculated in this way can also be used as the oxygen content (specifically, the proportion of oxygen ions in the anionic components (unit: anion %)). "Cation %" refers to the value calculated by "(the number of cations of interest / the total number of cations in the glass component) × 100", which is the molar percentage of the amount of cations of interest relative to the total amount of cations. Regarding the valence of the cationic component, the formal valence of each cation is used. The formal valence refers to the valence required for the oxide to maintain electrical neutrality when the valence of the oxygen ion (anion) constituting the oxide is set to -2 for the oxide of the cation of interest, and can be uniquely determined based on the chemical formula of the oxide. In addition, regarding the valence of the anion (e.g., the valence of the oxygen ion is -2, the valence of the fluorine ion is -1, and the valence of the chloride ion is -1), it is a formal valence based on the consideration that each ion accepts electrons to form a closed shell structure (e.g., a formal valence based on the consideration that the oxygen ion accepts 2 electrons to form a closed shell structure, and the fluorine ion and the chloride ion accept 1 electron to form a closed shell structure).

[0073] Alternatively, the content of the anion component may be defined by the content (unit: mass %) of each element as a percentage relative to 100 mass % of the total content of the glass composition based on the oxides of the cation components determined as described above.

[0074] In the present invention and this specification, the content of a constituent component being 0%, or not being contained or not being introduced means that the constituent component is not substantially contained, but inclusion of the constituent component at an unavoidable impurity level is permitted.

[0075] Generally speaking, SiO2-Na2O-CaO-based glasses are used as window glass and container glass. These glasses have a wetting angle of about 30° with respect to water and are generally considered to be hydrophilic. For glass containing more than 60% SiO2, no significant difference in the wetting angle is observed even when other components are adjusted, so it is inferred that no research has been conducted on improving the water repellency of the glass itself.

[0076] On the other hand, for lenses, prisms and optical fibers, glasses using network formers other than SiO2 have been used in the past. Glasses containing various components have characteristics in terms of refractive index and refractive index dispersion (changes in refractive index caused by the wavelength of light) and are used for lenses, prisms, optical fibers, etc.

[0077] Optical glass is often coated with an anti-reflection coating after grinding and polishing, and rarely comes into contact with water during use, so water repellency is not required. Therefore, the relationship between water repellency and glass composition has not been studied. For similar reasons, the relationship between water repellency and glass composition has not been studied for optical fibers.

[0078] The inventors have found that the wetting angle with respect to water varies depending on the composition of the glass, and have investigated the effects of different compositions. As a result, they have found that, for example, B2O3-La2O3-based glass tends to have high water repellency, while alkali components and SiO2 components tend to weaken water repellency. In addition, the inventors have found that it is also possible to obtain glass with good chemical durability against water. In other words, it has been found that it is possible to obtain glass useful for various applications that can take into account both water repellency and chemical durability in actual use when contact with water is a prerequisite.

[0079] In the above-mentioned glass, the main component of the network former may be any of SiO2, B2O3, and P2O5. B2O3 is particularly effective from the viewpoint that a large amount of La2O3 described later can be contained. From the viewpoint of suppressing the reduction of chemical durability, the B2O3 content is 35% or less, preferably 25% or less. In addition, the B2O3 content is 0% or more, preferably 8% or more.

[0080] From the viewpoint of improving the alkali resistance of glass, the B2O3 content may be 32% or less, 27% or less, 22% or less, 18% or less, or 15% or less.

[0081] SiO2 is effective as a glass network former. From the viewpoint of suppressing the decrease in water repellency, the SiO2 content is 25% or less, preferably 8% or less. The SiO2 content is 0% or more, preferably 1% or more.

[0082] From the viewpoint of improving the alkali resistance and / or chemical durability of the glass, the SiO2 content may be 2% or more, 4% or more, 10% or more, 15% or more, or 20% or more.

[0083] P2O5 is a useful component from the viewpoint of containing a large amount of BaO, CaO, Nb2O5 and other components described later. The P2O5 content is 0% or more and 30% or less from the viewpoint of improving chemical durability.

[0084] From the viewpoint of improving the alkali resistance of glass, the content of P2O5 is preferably 5% or less, more preferably 3% or less.

[0085] From the viewpoint of suppressing a decrease in water repellency, the total content of SiO2, B2O3 and P2O5 (SiO2+B2O3+P2O5) is in the range of 10 to 45%, preferably in the range of 10 to 40%, and more preferably in the range of 15 to 30%.

[0086] The GeO2 content is 0% or more. GeO2 has the function of stabilizing the glass as a network former, but is a rare component, so its content is 5% or less, preferably 2% or less, and more preferably less than 1%.

[0087] The Al2O3 content is 0% or more. Al2O3 is a component that can strengthen the structure of glass, and is therefore effective in improving chemical durability and mechanical strength. From the perspective of suppressing the crystallization tendency and stably producing, the Al2O3 content is 15% or less.

[0088] From the viewpoint of improving the alkali resistance of glass, the Al2O3 content may be more than 0%, 1% or more, or 3% or more.

[0089] The contents of Li2O, Na2O, K2O, Rb2O, and Cs2O are respectively above 0%. They are components that lower the melting temperature of glass and promote vitrification. From the viewpoint of suppressing the reduction of water repellency, suppressing the reduction of chemical durability, and suppressing the reduction of mechanical strength, the content of Li2O is below 2%, the content of Na2O is below 10%, the content of K2O is below 10%, the content of Rb2O is below 5%, and the content of Cs2O is below 5%.

[0090] From the viewpoint of suppressing the reduction of water repellency, suppressing the reduction of chemical durability and suppressing the reduction of mechanical strength, the total content of Li2O, Na2O, K2O, Rb2O and Cs2O (Li2O+Na2O+K2O+Rb2O+Cs2O) is in the range of 0 to 20%, preferably below 16%, more preferably below 9%, and further preferably below 6%.

[0091] From the perspective of improving the chemical durability of glass, the total content of Li2O, Na2O, K2O, Rb2O and Cs2O (Li2O+Na2O+K2O+Rb2O+Cs2O) can be less than 3%, less than 2%, less than 1% or less than 0.3%.

[0092] The ZnO content is 0% or more, preferably 3% or more, and more preferably 5% or more. ZnO is a component that improves water repellency, and even if the content of this component is high, stable vitrification can be achieved. From the viewpoint of suppressing the reduction of mechanical properties and suppressing the reduction of heat resistance (for example, suppressing the reduction of glass transition temperature), the ZnO content is 60% or less, preferably 55% or less, and more preferably 35% or less.

[0093] In one embodiment, the ZnO content may be 10% or more, 15% or more, 20% or more, 25% or more, 30%, 35% or more, 40% or more, or 45% or more.

[0094] In addition, in one embodiment, the ZnO content may be 40% or less, 32% or less, 24% or less, 16% or less, 8% or less, or 4% or less.

[0095] The contents of MgO, CaO, SrO, and BaO are respectively above 0%. They are effective components for achieving stable vitrification of any network formation. From the viewpoint of suppressing the reduction of water repellency, the MgO content is below 20%, the CaO content is below 25%, the SrO content is below 25%, and the BaO content is below 30%.

[0096] The La2O3 content is 0% or more, preferably 15% or more. La2O3 is a component that has a great effect of improving water repellency. From the viewpoint of suppressing the crystallization tendency, the La2O3 content is 50% or less, preferably 45% or less.

[0097] From the viewpoint of improving the alkali resistance of glass, the La2O3 content may be 10% or more, 15% or more, 20% or more, 25% or more, 33% or more, or 40% or more.

[0098] The contents of Y2O3 and Gd2O3 are respectively 0% or more. Y2O3 and Gd2O3 are components that can bring about the same effects as La2O3. From the viewpoint of suppressing the crystallization tendency, the content of Y2O3 is 15% or less and the content of Gd2O3 is 25% or less.

[0099] From the viewpoint of improving the alkali resistance of glass, the Y2O3 content may be 1% or more, 3% or more, or 4% or more.

[0100] From the viewpoint of improving the alkali resistance of glass, the Gd2O3 content may be 1% or more, 3% or more, or 4% or more.

[0101] The content of Yb2O3 is 0% or more. Yb2O3 can bring about the same effects as La2O3, Y2O3, and Gd2O3, but is a rare component, so its content is 10% or less, preferably 5% or less.

[0102] The CeO2 content is 0% or more. By adding a small amount of CeO2, the effect of shielding ultraviolet rays can be obtained. In addition, by adding a small amount of CeO2, the color of the glass can also be adjusted. From the perspective of suppressing the decrease in devitrification resistance, the CeO2 content is 5% or less.

[0103] The contents of Ga2O3 and In2O3 are respectively above 0%. Ga2O3 and In2O3 can bring about the same effects as La2O3, Y2O3, and Gd2O3, but they are rare components, so their contents are respectively below 5%.

[0104] The ZrO2 content is 0% or more, preferably 1% or more. ZrO2 is a component that can significantly improve chemical durability and mechanical strength (such as hardness) without significantly reducing water repellency. From the perspective of suppressing the increase in crystallization tendency due to the increase in melting temperature, the ZrO2 content is 15% or less, preferably 8% or less.

[0105] In addition, the ZrO2 content may be 2% or more, 4% or more, 5% or more, 6% or more, or 7% or more. ZrO2 is a component particularly useful for improving the chemical durability and / or alkali resistance of glass.

[0106] The TiO2 content is 0% or more. TiO2 is a component that can be contained in large amounts and is also a component that can improve chemical durability and mechanical strength. From the viewpoint of suppressing a decrease in transmittance, the TiO2 content is 20% or less.

[0107] In addition, the TiO2 content may be 2% or more, 4% or more, 6% or more, 8% or more, 10% or more, 12% or more, 16% or more, or 20% or more. This is because TiO2 is a useful component for improving the chemical durability and / or alkali resistance of glass.

[0108] The SnO2 content is 0% or more. SnO2 is a component that can bring about a clarifying effect by adding a small amount, and can also bring about an effect of improving water repellency. From the viewpoint of suppressing the decrease in solubility, the SnO2 content is 10% or less.

[0109] The Nb2O5 content can be 0% or more, 1% or more, 3% or more, 6% or more, 10% or more, or 14% or more. Nb2O5 can preferably be contained in large amounts in a glass having a P2O5 network, thereby providing a water-repellent effect. From the viewpoint of inhibiting the crystallization tendency, inhibiting the reduction in transmittance, and reducing costs, the Nb2O5 content is 30% or less, and can be 20% or less, 15% or less, or 10% or less.

[0110] The content of Ta2O5 is 0% or more. Ta2O5 can improve the stability of glass by adding a small amount. The content of Ta2O5 can be more than 0%, more than 1%, more than 3%, more than 6% or more than 12%. From the viewpoint of suppressing the tendency of crystallization, the content of Ta2O5 is less than 15%, and can also be less than 10%, less than 5% or 0%.

[0111] The WO3 content is 0% or more. WO3 can improve chemical durability by adding a small amount. The WO3 content can exceed 0%, 1% or more, 2% or more, or 4% or more. From the viewpoint of suppressing the rise in melting temperature and suppressing the tendency of crystallization, the WO3 content is 15% or less, and can also be 10% or less, 5% or less, or 0%.

[0112] The Bi2O3 content is 0% or more. Bi2O3 is a component that can improve the meltability without reducing the water repellency. From the viewpoint of suppressing the reduction of mechanical strength and suppressing the reduction of crystallization tendency, the Bi2O3 content is 20% or less, and can also be 14% or less, 9% or less, or 4% or less.

[0113] From the viewpoint of improving water repellency, the total content of ZnO, MgO, CaO, SrO, BaO, Y2O3, La2O3, Gd2O3, ZrO2, TiO2, Al2O3, Nb2O5, Ta2O5, WO3 and Bi2O3 (ZnO+MgO+CaO+SrO+BaO+Y2O3+La2O3+Gd2O3+ZrO2+TiO2+Al2O3+Nb2O5+Ta2O5+WO3+Bi2O3) is 55% or more, preferably 60% or more, and more preferably 65% ​​or more. From the viewpoint of suppressing the decrease in stability of the glass, the above total content is 90% or less, preferably 85% or less.

[0114] The content of Fe2O3 is in the range of 0 to 10%, and the total content of V2O5, Cr2O3, MnO2, Co2O3, NiO, CuO, MoO, Au2O3 and Ag2O (V2O5+Cr2O3+MnO2+Co2O3+NiO+CuO+MoO+Au2O3+Ag2O) is in the range of 0 to 3%. The color of the glass can be adjusted by appropriately adding one or more of Fe, V, Cr, Mn, Co, Ni, Cu, Mo, Au and Ag as coloring components. These components can usually be added as glass raw materials in the form of oxides or chlorides when manufacturing glass. The coloring can be adjusted by adjusting the melting temperature, atmosphere or heat treatment coloring, and various colors of glass can be obtained. In addition, as components that can be appropriately added to adjust the color of the glass, coloring components such as Nd2O3 can also be mentioned. In addition, Eu2O3, Er2O3, Sm2O3, etc. can also be mentioned.

[0115] The Sb2O3 content is 0% or more. Sb2O3, which can promote the clarification effect during melting, can be added up to 1%.

[0116] The above-mentioned glass can be obtained by mixing, melting and forming various glass raw materials. As glass raw materials, oxides, hydrates, phosphates, carbonates, nitrates, sulfates, fluorides, etc. can be used. Specific examples of glass raw materials include oxides such as SiO2, ZnO, La2O3, and ZrO2, hydrates such as H3BO3, nitrates such as Sr(NO3)2, carbonates such as BaCO3, etc. In addition, for example, by adding fluorides such as ZnF2, MgF2, and AlF3 as glass raw materials when manufacturing glass, glass containing fluorine can be obtained. The type and content of anionic components introduced into the glass can be adjusted by the type and addition amount of glass raw materials. As anionic components, oxygen (O 2- ), fluorine (F - ), chlorine (Cl - ) etc. In the above glass, regarding the anion component, oxygen (O 2- ) can be 100% anion, and can contain one or more other anion components in addition to oxygen. For example, fluorine (F - ) can contribute to the improvement of water repellency. From the viewpoint of suppressing the decrease in melt stability, suppressing the decrease in devitrification resistance, and suppressing the decrease in chemical durability, fluorine (F - ) content is preferably 30% or less of anions. As the content of the above-described addition ratio, the content of fluorine is preferably 10% by mass or less. In addition, chlorine (Cl - ) For example, AuCl3, AgCl and other chlorides can be introduced into the glass by using them as glass raw materials.

[0117] The above-mentioned glass can be amorphous glass in one embodiment, and can also be crystallized glass (crystallized glass) in another embodiment. In addition, the above-mentioned glass can be used in the form of a molded body of various shapes such as a plate shape by any molding method, can also be used in the form of a film (glass layer), and can also be used in the form of a glass powder. It can also be used in the form of a sintered body of glass powder, can also be used in the form of glass fiber, and can also be used in the form of a molded body of glass fiber. However, the above-mentioned glass does not include glass for optical elements selected from lenses and prisms and glass for optical fibers.

[0118] <Glass Properties>

[0119] (Wetting angle relative to water)

[0120] The wetting angle of the glass relative to water is 60° or more, preferably 65° or more, more preferably 70° or more, further preferably 75° or more, and further preferably 80° or more. In addition, the wetting angle of the glass relative to water may be, for example, 120° or less, 110° or less, 100° or less, 98° or less, or 95° or less. The larger the value of the wetting angle relative to water, the better the water repellency. Therefore, it is also preferred that the wetting angle relative to water exceeds the values ​​exemplified above.

[0121] In the present invention and this specification, the wetting angle of glass with respect to water is the contact angle measured within 30 seconds after 0.1 ml ± 0.02 ml of water is dropped on the glass surface in a measurement environment of an atmospheric temperature of 20°C ± 5°C and a relative humidity of 50% ± 20%. The arithmetic average of the values ​​obtained by three measurements is taken as the wetting angle of the glass with respect to water. The three measurements are performed at three different locations on the glass surface, or the measurements are repeated after the water dropped for the previous measurement is removed by drying or the like.

[0122] It should be noted that when the arithmetic mean roughness Ra of the surface of the glass to be measured for the wetting angle is below 0.2 μm, the wetting angle is measured on the surface. When the arithmetic mean roughness Ra of the surface of the glass to be measured for the wetting angle exceeds 0.2 μm, the surface is ground and polished until Ra reaches 0.2 μm or less, and then the wetting angle relative to water is measured on the polished surface. The arithmetic mean roughness Ra is a surface property parameter specified in JIS B 0601:2013. By obtaining the wetting angle relative to water for a surface with Ra of 0.2 μm or less, the water repellency of the glass itself can be evaluated with higher accuracy.

[0123] (Water resistance Dw)

[0124] In one embodiment, the glass may also have excellent water resistance. Water resistance can be evaluated by water resistance Dw obtained based on the Japan Optical Glass Industry Association Standard JOGIS-06:2019 "Method for Determination of Chemical Durability of Optical Glass (Powder Method)". In one embodiment, the water resistance Dw of the glass obtained in this way can be Class 1.

[0125] (Knoop hardness Hk)

[0126] In one embodiment, the above-mentioned glass can also have excellent mechanical strength. Mechanical strength can be evaluated by hardness, for example, and can be evaluated by Knoop hardness. For the hardness of the above-mentioned glass, the Knoop hardness calculated based on the Japan Optical Glass Industry Association Standard JOGIS-09:2019 "Determination Method of Knoop Hardness of Optical Glass" can be, for example, 450 or more, preferably 500 or more, and more preferably 550 or more. The Knoop hardness of the above-mentioned glass can be, for example, less than 850, less than 800, or less than 750, but it can also exceed the values ​​exemplified here. Glass with a large Knoop hardness value is not easy to be scratched, so it is preferred.

[0127] (Thermal Characteristics)

[0128] As an index of heat resistance, the glass transition temperature Tg can be cited. The glass transition temperature Tg is obtained as follows. In differential scanning calorimetry, when the glass sample is heated, an endothermic behavior accompanied by a change in specific heat, that is, an endothermic peak, appears, and when the temperature is further increased, an exothermic peak appears. In differential scanning calorimetry, a differential scanning calorimetry curve (DSC curve) is obtained in which the horizontal axis is set to temperature and the vertical axis is set to the amount corresponding to the exothermic endothermic of the sample. In this curve, the intersection of the tangent from the baseline to the point where the slope becomes the largest when the endothermic peak appears and the above-mentioned baseline is set as the glass transition temperature Tg. The determination of the glass transition temperature Tg can be carried out as follows: the glass is fully crushed with a mortar, etc., as a sample, and a differential scanning calorimeter is used, and the heating rate is set to 10°C / min. The glass transition temperature Tg of soda-lime glass is about 540°C. In contrast, the above-mentioned glass can be a glass with a glass transition temperature exceeding 550°C.

[0129] In addition, regarding thermal expansion characteristics, the average linear expansion coefficient α is a value measured using a thermomechanical analyzer (TMA) based on JOGIS-16:2019 "Method for determining the average linear expansion coefficient of optical glass near room temperature". Considering the small occurrence of cracks caused by thermal shock and sudden cooling, the average linear expansion coefficient α at -30 to 70°C is preferably 70×10 -7In one embodiment, the glass may have an average linear expansion coefficient α of 70×10 -7 / Glass below ℃.

[0130] The above-mentioned glass can obtain desired physical properties according to the intended use by appropriately adjusting its water repellency, chemical properties, mechanical properties, thermal properties, and the like.

[0131] (Alkali resistance)

[0132] In one embodiment, the above-mentioned glass can also have excellent alkali resistance. Regarding alkali resistance, the sample preparation method described in the Japanese Optical Glass Industry Association Standard JOGIS-06:2019 "Determination Method for Chemical Durability of Optical Glass (Powder Method)" can be used. Powdered glass (particle size 425-600 μm) with a mass equivalent to 1 cubic centimeter of optical glass is placed in a platinum basket and immersed in a NaOH aqueous solution with a concentration of 0.01 mol / l for 15 hours at a liquid temperature of 50°C. The mass reduction rate at this time (hereinafter referred to as "mass reduction rate in powder method alkali resistance test") is used as an indicator. In one embodiment, the mass reduction rate of the above-mentioned glass in the powder method alkali resistance test is preferably less than 0.10 mass%, and more preferably less than 0.02 mass%. For example, by making the content of glass components such as P2O5 in the range described above, it is easy to obtain glass with excellent alkali resistance.

[0133] [thing]

[0134] One embodiment of the present invention relates to an article containing glass. The article is selected from window materials, windshields, cover glasses, mirrors, tableware, physical and chemical experimental instruments, cooking utensils, washstands, toilet bowls, tombstones, decorations, arts and crafts, glass fibers, and glass fiber molded bodies, and the glass has the above-mentioned glass composition and has a wetting angle of 60° or more with respect to water. The glass composition and physical properties of the glass contained in the article are as described above for the glass of one embodiment of the present invention.

[0135] The above-mentioned articles are selected from window materials, windshields, cover glasses, mirrors, tableware, physical and chemical experimental instruments, cooking utensils, washstands, toilet bowls, tombstones, decorations, arts and crafts, glass fibers and glass fiber molded products. For example, the article may include the glass as window glass for buildings such as housing, display case glass, window materials such as shop window glass, car windshield, bus windshield, truck windshield, windshield for various operators, side glass, rear glass, tram windshield, tram window glass, airplane windshield, helicopter windshield, windshield and cover glass for drones, airplane window glass, helicopter window glass, windshield and window glass for ships such as high-speed ships, glass mirrors, mirrors with a glass layer as a surface layer, glass tableware, glass physical and chemical experimental equipment, glass cooking utensils, washstands, toilets, tombstones, necklaces, earrings, ear studs, rings and other ornaments, arts and crafts set outdoors or indoors, optical instruments set outdoors or indoors or used outdoors or indoors, cover glass of various articles, glass fiber molded bodies, etc. In one embodiment, the article may have a surface layer containing the glass.

[0136] For example, glass with excellent water repellency is most effective in automobile windshields.

[0137] The high water repellency and sliding properties make it easy to remove raindrops even when driving at low speeds.

[0138] In addition, the sliding of the wiper becomes better, and the durability of the wiper itself can also be improved with static action. By using glass with excellent water repellency for windshields of automobiles, etc., a comfortable field of vision can be obtained stably for a long time. These effects are also effective in side windows, rear windows, side mirrors, window materials for surveillance cameras, etc.

[0139] Water deposit is considered to be a phenomenon that occurs due to the combination of Si components contained in tap water, etc. and SiO2-based glass. In one embodiment, the glass may be a glass with low reactivity with Si, thereby suppressing the occurrence of water deposit.

[0140] The above-mentioned glass tends to have a higher specific gravity than soda-lime glass, and therefore the total weight tends to be larger, but this can provide an advantage of improved sound insulation.

[0141] In addition, glass with excellent water repellency can also be used as window materials for trams, airplanes, etc. Glass with excellent water repellency can be used as window materials for general buildings. Since it is effective in improving visual recognition on rainy days and can also reduce the residual dirt, it is also preferred in terms of long-term use. In addition, by reducing the content of the coloring components exemplified above, glass with high transmittance and less coloring can be obtained.

[0142] In addition, glass with excellent water repellency and water resistance is suitable for use as bathroom mirror glass. It can maintain the characteristics of easy viewing without water droplets remaining, and can also maintain excellent performance for long-term use. In addition, it is also effective in a visual recognition mirror set outdoors. In one embodiment, from the viewpoint of water resistance, the B2O3 content is preferably 25% or less.

[0143] For example, by melting the above-mentioned glass based on general soda-lime glass, dipping it, and implementing a given annealing, water repellency can be imparted to the surface of glass of various shapes. The above-mentioned glass can be a glass with a small surface free energy, so it can reduce the adhesion strength to various substances. The surface with small free energy feels smooth, fingerprint marks are not easy to adhere, and the attached marks are easy to remove. Utilizing this characteristic, it can be used for window materials of fingerprint authentication devices, cover glass of mobile phones, etc. In addition, the above-mentioned glass can also be used as tableware and container glass. Since it is easy to remove water after cleaning, it is also effective for reducing the cleaning burden and improving hygiene. In addition, in one embodiment, the above-mentioned glass can be a glass with a relatively high refractive index and large light scattering. If such glass is used as glasses (glass), a shining brilliance can be obtained. In addition, glass with high hardness is not easy to produce scratches, so long-term transparency can be obtained. Glass with a relatively large specific gravity is conducive to providing items with a high sense of weight. The use of glass with small thermal expansion can reduce the occurrence of cracks caused by rapid temperature changes. In addition, as one embodiment of the above-mentioned glass, glass having a total content of ZnO and La2O3 (ZnO+La2O3) of 60% or more tends to have a lower thermal conductivity and specific heat than soda-lime glass. Glass having a lower thermal conductivity and specific heat has a higher heat-insulating effect and has an effect of reducing the temperature difference at the moment of contact.

[0144] In addition, for teapots, having high water repellency on the surface is effective in reducing water dripping when hot water is poured in. Similarly, for cups and coffee cups, water dripping can be reduced by improving the water repellency on the surface.

[0145] In one embodiment, the surface of the glass may be processed according to the application. For example, the surface may be frosted with #60, #320, #800, #1200 abrasives or subjected to softening and pressurizing to impart fine concave and convex surfaces, thereby further inhibiting water wetting. Even as a frosted glass material for windows, it can provide excellent water repellency.

[0146] Furthermore, by appropriately mixing a coloring component into the above-mentioned glass, a colored article having water repellency can be obtained.

[0147] In one embodiment, the glass may be a crystal-containing glass. Crystal-containing glass is also generally referred to as crystallized glass, and compared with amorphous glass materials, there is a tendency to suppress the development of scars, so it is not easy to break. By adjusting the glass composition and the crystallization conditions, a crystal-containing glass useful as a building material such as an outer wall, floor material, roof material, etc. with desired water repellency, mechanical strength, and chemical durability can be obtained. In addition, by using crystal-containing glass for toilets, washstands, etc., the effect of reducing the adhesion of dirt and scale can be obtained.

[0148] In one embodiment, the glass may have a higher refractive index than soda-lime glass. Glass with a high refractive index has a characteristic of large light reflection. Such glass is preferably used as decorative glass for outdoor decoration.

[0149] The above-mentioned glass can be appropriately colored and its durability can be improved by adjusting its composition. By using such glass as a tombstone, a tombstone can be obtained which is difficult for dirt to adhere to, easy to clean, and can be kept clean for a long time.

[0150] In addition, by using the above glass as a powder material and applying it to various materials, a water-repellent coating can be formed. In addition, the coating can contribute to the improvement of heat resistance, etc. in addition to the improvement of water repellency.

[0151] Enamel using crystallized glass powder as a glaze can suppress adhesion of burnt matter.

[0152] By using glass with excellent water repellency, it is possible to suppress water from entering narrow gaps due to capillary phenomena, and by adjusting the glass composition according to the target liquid, it is also possible to adjust the surface tension, upward wetting, and intrusion of the liquid.

[0153] In glass measuring cylinders, burettes, eggplant-shaped flasks and other physical and chemical experimental instruments, the upward wetting of the meniscus makes it difficult to observe the storage, which sometimes makes accurate measurement difficult. However, using glass with excellent water repellency can enable accurate measurement. In this case, it is particularly preferred that the wetting angle relative to water is about 90° (for example, about 85° to 95°). This also applies to measuring instruments for cooking, which are a type of cooking utensils.

[0154] The material obtained by molding the above-mentioned glass into fibers and the fibers formed therefrom can be used for various molded bodies for ships, glass wool thermal insulation materials with high heat insulation properties, and the like, utilizing the property of being less likely to be wetted by water.

[0155] Glass fiber made of glass with excellent alkali resistance is useful as glass fiber for cement reinforcement. In addition, glass with excellent alkali resistance has high tolerance to alkaline soapy water, and therefore, is also useful as a material for glass bathroom mirrors, a material for the surface layer of bathroom mirrors, etc.

[0156] Example

[0157] Hereinafter, the present invention will be described in more detail with reference to examples, but the present invention is not limited to the embodiments of the examples.

[0158] For Examples 1 to 47 and Comparative Examples 1 to 5, the raw materials for introducing each component were weighed and fully mixed so as to obtain the glass compositions shown in Table 1 (Table 1-1 to Table 1-4) below, respectively, to prepare the blended raw materials. As the raw materials, oxides of the components were used except for Example 8. For Example 8, ZnO and ZnF2 were used as Zn raw materials, and oxides of the components were used as other raw materials.

[0159] 100 to 200 g of the prepared raw materials were melted at 1200 to 1400° C. using a platinum crucible, poured into an iron mold, and annealed after molding to produce a glass plate.

[0160] The glass constituting the glass plates of Examples 12, 22, 26, and 28 is crystallized glass, and the glass constituting the glass plates of the other Examples is amorphous glass.

[0161] The wetting angle with respect to water, the water resistance Dw, and the Knoop hardness Hk of the produced glass plate were determined by the methods described above.

[0162] About the glass plates of Examples 1 to 39, the mass reduction rate in the powder method alkali resistance test was determined by the method described above.

[0163] In addition, for the glass plate of Example 10, the water sliding property was measured in a measurement environment with an ambient temperature of 20°C±5°C and a relative humidity of 50%±20%. The results confirmed that a 0.1 ml water droplet slid down when the surface of the glass plate was tilted at an angle of 40° relative to the horizontal plane (water sliding angle).

[0164] In the following tables, the unit of content is mass %. In addition, "A" represents the total content of SiO2, B2O3 and P2O5 (SiO2+B2O3+P2O5), "B" represents the total content of ZnO, MgO, CaO, SrO, BaO, Y2O3, La2O3, Gd2O3, ZrO2, TiO2, Al2O3, Nb2O5, Ta2O5, WO3 and Bi2O3 (ZnO+MgO+CaO+SrO+BaO+Y2O3+La2O3+Gd2O3+ZrO2+TiO2+Al2O3+Nb2O5+Ta2O5+WO3+Bi2O3), and "C" represents the total content of Li2O, Na2O, K2O, Rb2O and Cs2O (Li2O+Na2O+K2O+Rb2O+Cs2O).

[0165] In the following tables, the numerical values ​​written as "Dw" indicate the level of Dw. That is, "1" indicates level 1, and "3" indicates level 3.

[0166]

[0167]

[0168]

[0169]

[0170] As shown in Table 1, the wetting angles of the glasses of Examples with respect to water were all 60° or more.

[0171] As Reference Example 1, the wetting angle of stainless steel SUS304 with respect to water was similarly determined and found to be 68°.

[0172] As Reference Example 2, the wetting angle with respect to water was similarly determined for PTFE (polytetrafluoroethylene) which is generally regarded as a water-repellent material, and the result was 90°.

[0173] From the above results, it was confirmed that the water repellency of the glass of the example is as excellent as that of materials known as materials with high water repellency.

[0174] Comparative Example 1 is an optical glass with SiO2 exceeding 60% (equivalent to the material of BSC7 manufactured by HOYA Corporation). The SiO2 content is high, and the total content of Li2O, Na2O, K2O, Rb2O and Cs2O (Li2O+Na2O+K2O+Rb2O+Cs2O) is also high.

[0175] In the glass composition of Comparative Example 2, the P2O5 content is high, and the total content of SiO2, B2O3 and P2O5 (SiO2+B2O3+P2O5) is also high.

[0176] In the glass composition of Comparative Example 3, the total content of SiO2, B2O3 and P2O5 (SiO2+B2O3+P2O5) is high.

[0177] In the glass composition of Comparison Example 4 and the glass composition of Comparison Example 5, the total content of ZnO, MgO, CaO, SrO, BaO, Y2O3, La2O3, Gd2O3, ZrO2, TiO2, Al2O3, Nb2O5, Ta2O5, WO3 and Bi2O3 (ZnO+MgO+CaO+SrO+BaO+Y2O3+La2O3+Gd2O3+ZrO2+TiO2+Al2O3+Nb2O5+Ta2O5+WO3+Bi2O3) is small.

[0178] Comparative Example 6 is a commercially available soda-lime glass having a SiO2 content exceeding 70% and a combined content of Li2O, Na2O, K2O, Rb2O and Cs2O (Li2O+Na2O+K2O+Rb2O+Cs2O).

[0179] The glasses of Comparative Examples 1 to 6 having the above glass compositions all had wetting angles with respect to water of less than 60° and were inferior in water repellency to the glasses of the examples.

[0180] It was also confirmed that the mass reduction rate of the glass of the examples in the powder method alkali resistance test was 0.10 mass% or less, and the alkali resistance was excellent. It should be noted that the powder method alkali resistance test was also carried out on blue plate glass generally used as window material, and the mass reduction rate was 0.25 mass%.

[0181] For the glasses of Examples 40 to 47, 2.5 mm thick glass plates were produced by the above method, and the spectral transmittance of the produced glasses was measured to obtain spectral transmittance curves ( Figures 1 to 8 ).

[0182] according to Figures 1 to 8 The spectral transmittance curve shown in the figure confirms that the absorption characteristics of glass can be variously changed by adding a component useful for color adjustment, that is, the color of glass can be easily adjusted.

[0183] Finally, the above-mentioned embodiments are summarized.

[0184] According to one embodiment, a glass is provided, wherein in an oxide-based glass composition, on a mass basis, a SiO2 content is 0 to 25%, a B2O3 content is 0 to 35%, a P2O5 content is 0 to 30%, a total content of SiO2, B2O3 and P2O5 (SiO2+B2O3+P2O5) is 10 to 45%, an Al2O3 content is 0 to 15%, a Li2O content is 0 to 2%, a Na2O content is 0 to 10%, a K2O content is 0 to 10%, a Rb2O content is 0 to 5%, a Cs2O content is 0 to 5%, and Li2O, Na2O, K2O, Rb2O and Cs2 The total content of O (Li2O+Na2O+K2O+Rb2O+Cs2O) is 0-15%, the content of MgO is 0-20%, the content of CaO is 0-25%, the content of SrO is 0-25%, the content of BaO is 0-30%, the content of ZnO is 0-60%, the content of La2O3 is 0-50%, the content of Y2O3 is 0-15%, the content of Gd2O3 is 0-25%, the content of Yb2O3 is 0-10%, the content of CeO2 is 0-10%, the content of ZrO2 is 0-15%, the content of TiO2 is 0-20%, the content of SnO2 is 0-10%, and the content of Nb2O5 is 0-3 0%, Ta2O5 content is 0-15%, WO3 content is 0-15%, Bi2O3 content is 0-20%, Ga2O3 content is 0-5%, In2O3 content is 0-5%, GeO2 content is 0-5%, Sb2O3 content is 0-1%, the total content of ZnO, MgO, CaO, SrO, BaO, Y2O3, La2O3, Gd2O3, ZrO2, TiO2, Al2O3, Nb2O5, Ta2O5, WO3 and Bi2O3 (ZnO+MgO+CaO+SrO+BaO+Y2O3+La2O3+Gd2O3+ZrO2 +TiO2+Al2O3+Nb2O5+Ta2O5+WO3+Bi2O3) is 55-90%, the Fe2O3 content is 0-10%, the total content of V2O5, Cr2O3, MnO2, Co2O3, NiO, CuO, MoO, Au2O3 and Ag2O (V2O5+Cr2O3+MnO2+Co2O3+NiO+CuO+MoO+Au2O3+Ag2O) is 0-3%, and the wetting angle of the above-mentioned glass relative to water is greater than 60°, wherein the above-mentioned glass does not include glass for optical elements selected from lenses and prisms and glass for optical fibers.

[0185] The above-mentioned glass can exhibit excellent water repellency.

[0186] In one embodiment, an article comprising glass is provided. The article is selected from window materials, windshields, cover glasses, mirrors, tableware, physical and chemical experimental instruments, cooking utensils, washstands, toilet bowls, tombstones, decorations, arts and crafts, glass fibers, and glass fiber molded bodies. In the glass composition based on oxides of the glass, the content of SiO2 is 0-25%, the content of B2O3 is 0-35%, the content of P2O5 is 0-30%, the total content of SiO2, B2O3 and P2O5 (SiO2+B2O3+P2O5) is 10-45%, the content of Al2O3 is 0-15%, the content of Li2O is 0-2%, the content of Na2O is 0-10%, the content of K2O is 0-10%, and the content of The content is 0-10%, the content of Rb2O is 0-5%, the content of Cs2O is 0-5%, the total content of Li2O, Na2O, K2O, Rb2O and Cs2O (Li2O+Na2O+K2O+Rb2O+Cs2O) is 0-15%, the content of MgO is 0-20%, the content of CaO is 0-25%, the content of SrO is 0-25%, the content of BaO is 0-30%, the content of ZnO is 0-60%, the content of La2O3 is 0-50%, the content of Y2O3 is 0-15%, the content of Gd2O3 is 0-25%, the content of Yb2O3 is 0-10%, the content of CeO2 is 0-10%, The content of ZrO2 is 0-15%, the content of TiO2 is 0-20%, the content of SnO2 is 0-10%, the content of Nb2O5 is 0-30%, the content of Ta2O5 is 0-15%, the content of WO3 is 0-15%, the content of Bi2O3 is 0-20%, the content of Ga2O3 is 0-5%, the content of In2O3 is 0-5%, the content of GeO2 is 0-5%, the content of Sb2O3 is 0-1%, and the total content of ZnO, MgO, CaO, SrO, BaO, Y2O3, La2O3, Gd2O3, ZrO2, TiO2, Al2O3, Nb2O5, Ta2O5, WO3 and Bi2O3 The content of (ZnO+MgO+CaO+SrO+BaO+Y2O3+La2O3+Gd2O3+ZrO2+TiO2+Al2O3+Nb2O5+Ta2O5+WO3+Bi2O3) is 55~90%, the content of Fe2O3 is 0~10%, the total content of V2O5, Cr2O3, MnO2, Co2O3, NiO, CuO, MoO, Au2O3 and Ag2O (V2O5+Cr2O3+MnO2+Co2O3+NiO+CuO+MoO+Au2O3+Ag2O) is 0~3%, and the wetting angle of the above glass relative to water is above 60°.

[0187] The glass and the glass included in the above-mentioned article may be in the following embodiments.

[0188] In one embodiment, the total content of SiO2, B2O3 and P2O5 (SiO2+B2O3+P2O5) is 10-35%, and the total content of ZnO, MgO, CaO, SrO, BaO, Y2O3, La2O3, Gd2O3, ZrO2, TiO2, Al2O3, Nb2O5, Ta2O5, WO3 and Bi2O3 (ZnO+MgO+CaO+SrO+BaO+Y2O3+La2O3+Gd2O3+ZrO2+TiO2+Al2O3+Nb2O5+Ta2O5+WO3+Bi2O3) is 55-85%.

[0189] In one embodiment, the SiO2 content is 1-8%, the B2O3 content is 8-25%, the ZnO content is 3-35%, the La2O3 content is 15-45%, the ZrO2 content is 1-8%, the total content of SiO2, B2O3 and P2O5 (SiO2+B2O3+P2O5) is 15-30%, and the total content of ZnO, MgO, CaO, SrO, BaO, Y2O3, La2O3, Gd2O3, ZrO2, TiO2, Al2O3, Nb2O5, Ta2O5, WO3 and Bi2O3 (ZnO+MgO+CaO+SrO+BaO+Y2O3+La2O3+Gd2O3+ZrO2+TiO2+Al2O3+Nb2O5+Ta2O5+WO3+Bi2O3) is 65-85%.

[0190] In one embodiment, the wetting angle of the glass with respect to water may be greater than 80°.

[0191] In one embodiment, the water resistance Dw of the glass may be level 1.

[0192] In one embodiment, the Knoop hardness Hk of the glass may be 450 or more or 550 or more.

[0193] In one embodiment, the glass may have a mass reduction rate of 0.10 mass % or less in a powder method alkali resistance test.

[0194] It should be understood that the embodiments disclosed herein are all exemplary and do not constitute limitations. The scope of the present invention is defined by the claims rather than the above description, and is intended to include all modifications within the meaning and scope equivalent to the claims.

[0195] For example, by adjusting the composition of the glasses exemplified above as described in the specification, the glass according to one embodiment of the present invention can be obtained.

[0196] Furthermore, it is of course possible to arbitrarily combine two or more of the items exemplified in the specification or described as preferred ranges or embodiments.

Claims

1. A glass having an oxide-based glass composition: Based on quality standards, SiO2 content is 0~25%, B2O3 content is 0~35%, P2O5 content is 0~30%, The total content of SiO2, B2O3 and P2O5 (SiO2+B2O3+P2O5) is 10-45%, Al2O3 content is 0~15%, Li2O content is 0-2%, Na2O content is 0-10%, K2O content is 0-10%, Rb2O content is 0-5%, Cs2O content is 0-5%, The total content of Li2O, Na2O, K2O, Rb2O and Cs2O (Li2O+Na2O+K2O+Rb2O+Cs2O) is 0-15%, MgO content is 0-20%, CaO content is 0-25%, SrO content is 0-25%, BaO content is 0-30%, ZnO content is 0-60%, La2O3 content is 0~50%, Y2O3 content is 0~15%, Gd2O3 content is 0~25%, Yb2O3 content is 0~10%, CeO2 content is 0~10%, ZrO2 content is 0~15%, TiO2 content is 0-20%, SnO2 content is 0~10%, Nb2O5 content is 0~30%, Ta2O5 content is 0~15%, WO3 content is 0-15%, Bi2O3 content is 0~20%, Ga2O3 content is 0~5%, In2O3 content is 0~5%, GeO2 content is 0~5%, The content of Sb2O3 is 0-1%, The total content of ZnO, MgO, CaO, SrO, BaO, Y2O3, La2O3, Gd2O3, ZrO2, TiO2, Al2O3, Nb2O5, Ta2O5, WO3 and Bi2O3 (ZnO+MgO+CaO+SrO+BaO+Y2O3+La2O3+Gd2O3+ZrO2+TiO2+Al2O3+Nb2O5+Ta2O5+WO3+Bi2O3) is 55-90%, Fe2O3 content is 0~10%, The total content of V2O5, Cr2O3, MnO2, Co2O3, NiO, CuO, MoO, Au2O3 and Ag2O (V2O5+Cr2O3+MnO2+Co2O3+NiO+CuO+MoO+Au2O3+Ag2O) is 0-3%, Furthermore, the wetting angle of the glass relative to water is greater than 60°. The glass does not include glass used for optical elements selected from lenses and prisms and glass used for optical fibers.

2. The glass according to claim 1, wherein: The total content of SiO2, B2O3 and P2O5 (SiO2+B2O3+P2O5) is 10-35%, The total content of ZnO, MgO, CaO, SrO, BaO, Y2O3, La2O3, Gd2O3, ZrO2, TiO2, Al2O3, Nb2O5, Ta2O5, WO3 and Bi2O3 (ZnO+MgO+CaO+SrO+BaO+Y2O3+La2O3+Gd2O3+ZrO2+TiO2+Al2O3+Nb2O5+Ta2O5+WO3+Bi2O3) is 55-85%.

3. The glass according to claim 1 or 2, wherein: SiO2 content is 1-8%, B2O3 content is 8-25%, ZnO content is 3-35%, La2O3 content is 15-45%, The ZrO2 content is 1-8%, The total content of SiO2, B2O3 and P2O5 (SiO2+B2O3+P2O5) is 15-30%, The total content of ZnO, MgO, CaO, SrO, BaO, Y2O3, La2O3, Gd2O3, ZrO2, TiO2, Al2O3, Nb2O5, Ta2O5, WO3 and Bi2O3 (ZnO+MgO+CaO+SrO+BaO+Y2O3+La2O3+Gd2O3+ZrO2+TiO2+Al2O3+Nb2O5+Ta2O5+WO3+Bi2O3) is 65~85%. 4 . The glass according to claim 1 , wherein the glass has a wetting angle with respect to water of 80° or more. The glass according to any one of claims 1 to 4, which has a water resistance Dw of Class 1. The glass according to any one of claims 1 to 5, which has a Knoop hardness Hk of 450 or more. 7 . The glass according to claim 1 , which has a Knoop hardness Hk of 550 or more. 8 . The glass according to claim 1 , wherein the glass has a mass reduction rate of 0.10 mass % or less in a powder method alkali resistance test.

9. An article containing glass, The article is selected from window materials, windshields, cover glasses, mirrors, tableware, physical and chemical experimental instruments, cooking utensils, washstands, toilet bowls, tombstones, decorations, arts and crafts, glass fibers and glass fiber molded bodies, In the oxide-based glass composition of the glass, Based on quality standards, SiO2 content is 0~25%, B2O3 content is 0~35%, P2O5 content is 0~30%, The total content of SiO2, B2O3 and P2O5 (SiO2+B2O3+P2O5) is 10-45%, Al2O3 content is 0~15%, Li2O content is 0-2%, Na2O content is 0-10%, K2O content is 0-10%, Rb2O content is 0-5%, Cs2O content is 0-5%, The total content of Li2O, Na2O, K2O, Rb2O and Cs2O (Li2O+Na2O+K2O+Rb2O+Cs2O) is 0-15%, MgO content is 0-20%, CaO content is 0-25%, SrO content is 0-25%, BaO content is 0-30%, ZnO content is 0-60%, La2O3 content is 0~50%, Y2O3 content is 0~15%, Gd2O3 content is 0~25%, Yb2O3 content is 0~10%, CeO2 content is 0~10%, ZrO2 content is 0~15%, TiO2 content is 0-20%, SnO2 content is 0~10%, Nb2O5 content is 0~30%, Ta2O5 content is 0~15%, WO3 content is 0-15%, Bi2O3 content is 0~20%, Ga2O3 content is 0~5%, In2O3 content is 0~5%, GeO2 content is 0~5%, The content of Sb2O3 is 0-1%, The total content of ZnO, MgO, CaO, SrO, BaO, Y2O3, La2O3, Gd2O3, ZrO2, TiO2, Al2O3, Nb2O5, Ta2O5, WO3 and Bi2O3 (ZnO+MgO+CaO+SrO+BaO+Y2O3+La2O3+Gd2O3+ZrO2+TiO2+Al2O3+Nb2O5+Ta2O5+WO3+Bi2O3) is 55-90%, Fe2O3 content is 0~10%, The total content of V2O5, Cr2O3, MnO2, Co2O3, NiO, CuO, MoO, Au2O3 and Ag2O (V2O5+Cr2O3+MnO2+Co2O3+NiO+CuO+MoO+Au2O3+Ag2O) is 0-3%, Furthermore, the wetting angle of the glass with respect to water is greater than 60°.

10. The article according to claim 9, wherein In the glass, The total content of SiO2, B2O3 and P2O5 (SiO2+B2O3+P2O5) is 10-35%, The total content of ZnO, MgO, CaO, SrO, BaO, Y2O3, La2O3, Gd2O3, ZrO2, TiO2, Al2O3, Nb2O5, Ta2O5, WO3 and Bi2O3 (ZnO+MgO+CaO+SrO+BaO+Y2O3+La2O3+Gd2O3+ZrO2+TiO2+Al2O3+Nb2O5+Ta2O5+WO3+Bi2O3) is 55-85%.

11. The article according to claim 9 or 10, wherein In the glass, SiO2 content is 1-8%, B2O3 content is 8-25%, The ZnO content is 3-35%, La2O3 content is 15-45%, The ZrO2 content is 1-8%, The total content of SiO2, B2O3 and P2O5 (SiO2+B2O3+P2O5) is 15-30%, The total content of ZnO, MgO, CaO, SrO, BaO, Y2O3, La2O3, Gd2O3, ZrO2, TiO2, Al2O3, Nb2O5, Ta2O5, WO3 and Bi2O3 (ZnO+MgO+CaO+SrO+BaO+Y2O3+La2O3+Gd2O3+ZrO2+TiO2+Al2O3+Nb2O5+Ta2O5+WO3+Bi2O3) is 65~85%.

12. The article according to any one of claims 9 to 11, wherein The wetting angle of the glass with respect to water is 80° or more.

13. The article according to any one of claims 9 to 12, wherein The water resistance Dw of the glass is grade 1.

14. The article according to any one of claims 9 to 13, wherein The glass has a Knoop hardness Hk of 450 or more.

15. The article according to any one of claims 9 to 14, wherein The glass has a Knoop hardness Hk of 550 or more.

16. The article according to any one of claims 9 to 15, wherein The glass has a mass reduction rate of 0.10 mass % or less in a powder method alkali resistance test.

Citation Information

Patent Citations

  • Water-repellent member

    JP2017001327A

Cited By

  • Electronic-grade glass fiber composition, glass fiber cloth and preparation method thereof

    CN121248146A